Effects of selected factors on the mycelial incubation of Lentinula edodes (Berk.) Pegler pegler under laboratory conditions - Phuong Le, Linh Thi; Thanh Nguyen, Tra Thi; Thuong Vu, Thi (Academia Journal of Biology, 2026)
In this paper, we studied the effects of substrate composition and ratio on the mycelium growth of Letinula edodes (Berk) Pegler. The experiment was conducted in laboratory conditions. We monitored quantitative indicators, including mycelium spreading speed, coverage and observed mycelium characteristics. Then, we statistically analyzed to evaluate the influence of the experimental formulas. We arranged 4 different substrate formulas. The experimental results showed that formula 4 (69% sawdust, 15% corn cob, 15% rice bran, 1% CaCO3) was best for the mycelium growth of shiitake mushrooms. The coverage of the mycelium in formula 4 at 5, 10, 15 and 20 days was 18.0, 40.0, 66.7, 94.7%, respectively. The mycelium spreading rate in formula 4 at 5, 10, 15 and 20 days was 5.4 mm/day, 6.6 mm/day, 8.0 mm/day, 8.4 mm/day, respectively. Substrate formula number 4 was used to conduct experiments on the influence of bag density. The bag density with the highest mycelium spreading rate was 25 bags/m2. In addition, we also conducted research on the influence of temperature on the development of the mycelium of shiitake mushrooms. The experiment was conducted in laboratory conditions. The temperature was controlled by air conditioning. The most suitable temperature for mycelium development was 25–27 oC. The results of this study are the basis for making the best decisions in shiitake mushroom production, improving productivity and economic efficiency.